A preprocessor for parametric composite rotor blade cross-sections - Pflumm, T.; Garre, W.; Hajek, M. (My University, 2018)
Structural helicopter rotor blade optimization comprises classical aeroelastic problems, where the aerodynamic behavior, the structural elasticity and vibrational dynamics have to be studied simultaneously. Since the dynamic and modal behavior is strongly related to the structural properties of the rotor blades, adjusting these properties is essential for an effective optimization. Nevertheless, identifying constraints based on elemental matrices to keep the solution within feasible boundaries is often a protracted and iterative task. In this paper a structural preprocessor for parametric analysis and design of composite beam cross-section is presented. The herein presented definition of the rotor blade topology is deliberately associated to the production of composite rotor blades. Thus, manufacturability is inherent from the geometric layup definition. Using orthogonal projection with corner-style differentiation the cross-section is discretized and processed by the Variational Asymptotic Beam Sectional Analysis (VABS) afterwards. The approach is successfully demonstrated with generic UH-60A composite rotor blade cross-sections.